Sustainability in arctic maritime supply chains - Jürgen Weigell; Igor Ilin; Svetlana Maydanova; Alissa Dubgorn; Carlos Jahn; Wolfgang Kersten (Data Science in Maritime and City Logistics: Data-driven Solutions for Logistics and Sustainability. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 30, 2020)
Purpose: The sustainable development of Arctic maritime supply chains requires an effective balance between economic growth, environmental protection and social relations. Existing Arctic development projects are often distinguished by single-criterion decision making - economic growth to the detriment of other components. The paper aims to analyze existing approaches and practices of Arctic supply chains development from a sustainable development viewpoint. Methodology: Best practices of other industries are identified by a thoroughly literature research of relevant publications and developing a model for sustainability issues in Arctic maritime supply chains. The model compromises relevant indicators in regard to economic, social and environmental performance for the Arctic region. Findings: The result of this paper will be a thoroughly overview over current sustainability issues in the Arctic framework (economic, social and environmental). Findings for example will be how companies adjust to the ban of using heavy Sulphur fuel in the Arctic or social and economic changes in remote areas due to more shipping in the Arctic. Originality: The originality of the research is defined by the sustainability viewpoint on the problem: the combination of social, economic as well as environmental issues is the main focus of this paper especially with a focus on remote areas of the Arctic.
urn:nbn:de:gbv:830-882.0115606; hdl:10419/228915; https://econpapers.repec.org/RePEc:zbw:hiclpr:30
Keywords: 650; Logistics; Industry 4.0; Supply Chain Management; Sustainability; City Logistics; Maritime Logistics; Data Science